I carpenter a space for the thing I am given : influence and the consciousness of space in Emily Dickenson, H. D. and Sylvia Plath - O'Reilly, Caitríona, 1973- (Trinity College (Dublin, Ireland). School of English, 2002)
The introduction indicates the context from which my examination of the continuities between Emily Dickinson, H.D., and Sylvia Plath arose; it does so by stating the principal areas of difference between this thesis and previous studies of influence in American poetry. It highlights the significance of consciousness in the work of all three writers, linking this, with reference to Gaston Bachelard’s The Poetics of Space (1957), to the prevalence and consistency of spatial imagery in their poetry and prose. My introduction proposes a more flexible phenomenological, rather than a strict psychoanalytical approach to the study of influence in the writers I am examining. In the first chapter I state the terms of my confi-ontation with previous studies of influence, detailing the way in which a phenomenological approach to the three writers under consideration allows a greater illumination of their lines of continuity, as well as their significant departures from each other. In this chapter I engage with Harold Bloom’s theories of literary influence, scrutinising the strongly Freudian basis of his criticism. I then move to an examination of the subsequent influence-theories of Susan Gilbert and Sandra Gubar (the ‘Female Affiliation Complex’), and Joanne Feit Diehl’s Kleinian method, as demonstrated in her analysis of the Marianne Moore-Elizabeth Bishop relationship. This chapter concludes by engaging with Gaston Bachelard’s essay on his phenomenological approach to poetic imagery in The Poetics of Space, and states the usefulness of this as an alternative critical method.
Keywords: English, Ph.D.; Ph.D. Trinity College Dublin